ЦОКОЛЬНОЕ ПОДНЯТИЕ МОНГОЛО-СИБИРСКОГО ВОЗРОЖДЕННОГО ОРОГЕНА - Уфимцев Г.Ф.; Щетников А.А. (My University, 1999)
The principal peculiarity of the deep-seated structure of the Mongol-Siberian belt of rejuvenated mountains is a large asthenolith occurring under the belt lithosphere. The asthenolith causes a general dome-shaped uplifting of the mountain belt socle. The amplitudes of these uplifts conditioned by extension and common unconsolidation of the earth’s crust and the upper mantle with asthenolith formation have been calculated.
Keywords: 551.248.2(1-925.32)